Implementasi Senam Hamil Gerakan Sholat dalam Normalisasi Denyut Jantung Janin - Arum Meiranny; RR. Catur Leny Wulandari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Anxiety that is not resolved immediately in pregnant women and the inability to regulate the breathing pattern can affect the condition of the intrauterine fetus, so it must be addressed immediately. The number of pregnant women who have a gestation of more than 20 weeks at Limbangan Community Health Center is 20 people. Fetal Heart Rate (FHR) at arrival ranges from 120-160 x/minute; due to fatigue and inability to regulate breathing patterns, some pregnant women feel anxious. The solution to this problem is aimed at normalizing the DJJ by doing pregnancy exercises, prayer movements. The implementation of activities with the application of science and technology was carried out twice, on 4 September 2020 and 2 October 2020, with the target of pregnant women at the Puskesmas Limbangan Kendal Regency. The form of science and technology transfer began with a pre-test and ended with a post-test; education was delivered in an easy-to-understand method, providing material on prenatal exercise with prayer movements. All participants also immediately performed pregnancy exercises during the prayer movements according to instructions from the proposing team. In addition, fellow participants also discussed and exchanged experiences about their pregnancies. FHR for pregnant women ranges from 130-150 x/minute after the prayer movements; participants feel calmer and more comfortable because their breathing patterns are regular. The most important thing in this activity is that the mother will teach other pregnant women.